All The Trees Are Falling Down: Environmental Concern of A Malaysian Poet - Arifin, Mohammad Sidik (Jurnal Peradaban Melayu, 2010)
Literature shares a similarity with other disciplines in the social sciences since it looks into the social, political and economics aspects of human society. Literature creatively highlights pertinent issues in society, and portrays human feelings in interactions in family and community life. According to the Malaysian National Laureate, Shahnon Ahmad, literature is viewed as life’s seismograph. Literary works like the novel, short story and poetry have the characteristics of a seismograph, an instrument in geological studies which records about earthquakes. A seismograph only records earthquakes as a natural disaster whereas literary works register and analyze ’earthquakes’ of life. These ’earthquakes’ refer to all types of obstacles and challenges in man’s life for instance the hardship faced by the poor and destitute. (Shahnon 1994: 3). Similarly the poems selected for discussion in this essay would serve as a seismograph which records and highlight environmental issues. Literary works written in Malaysia since independence are abound with relevant issues of the particular era. For instance, a novel, Scorpion Orchid (1992) by Llyod Fernando dwelled on the problems of race relations and nation building. Ee Tiang Hong’s poem, ’Exile’ shows the ’linguistic exile’ which refers to the poet’s protest and dissatisfaction with government bureaucracy and political institutions. (Kirpal Singh 2001: 227). A Malay poet, Muhammad Haji Salleh, in his anthology, Rowing Down neo Rivers (2000), focuses on the Malay identity and voices out his feelings of discontentment in the issue of Malay poverty and economic inequality. This essay shall focus on a number of poems with environmental and ecological concern selected from the anthology ’Rags and Ragas’ (2000) written by a Malaysian poet, Cecil Rajendra. He has contributed to the growth ofpoetry in Malaysian literature in English, from the 1970’s to the 1990’s. However, there is a uniqueness in his poems, in contrast to other local poets. He focused on issues, some of which might be sensitive to the powers that be, such as politics and government policies in Malaysia. Although similar issues have been touched on by other poets before him, it was done subtly as compared to his poems which criticize and lambast directly. As discussed earlier in the themes preferred by Malaysian poets, it can be said that Malaysian poets in English worked only on communal themes based on the ethnicity of the poet. For instance Malay poets focused on rural life and patriotism while the descendants of the Chinese or Indian immigrants would look into matters of identity, alienation, ambivalence and their associations with their parent country. On the contrary, the predominant themes in the works of Cecil Rajendra are no more issues of pre-independence and post-independence days such as ethnicity, but are more Malaysian in character with a wider universal appeal. He has dealt with matters of concern for every Malaysian for instance, human rights, justice and equality. Cecil Rajendra is a lawyer by profession and is an active member of the Malaysian Bar Council. As such he is not a full-time poet. Nevertheless he is committed in using literary works such as poetry as a tool for criticism of society’s follies. He is much involved in voluntary service such as providing free legal aid to poor fishermen and factory workers in his home state, Penang. During his sojourn in London, he was involved with Third World writers and poets. He was the first Malaysian poet to gain recognition by the national Poetry Secretariat of Great Britain and Northern Ireland. His poems, mostly of Third World concern, have been published and broadcasted in over thirty-six countries and also translated into other languages (Rajendra 1989: 1-2). He has been a prolific poet with not less than thirteen anthologies of his poems published since 1965. Most of his poetry collections deal with issues of war, poverty, inequality and social injustice. Nevertheless, one of his favourite concerns is environmental issues, particularly in matters of forest conservation and ecological balance. Ecological ruin such as indiscriminate tree felling, land clearing, emission of hazardous gases and the like are some of the themes in his poems (Fadillah et. al 2004: 90). He has presented these themes through irony and satire in his poems.